Self-Acceptance and Resilience in Students Working on Their Thesis - Guykens, Paul Willyam; Murti, Heru Astikasari Setya (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
During the thesis work, students will be faced with various demands. The demands faced by students are in the form of rules that must be met in working on the thesis, pressure from parents, and self-standards that must be achieved when working on the thesis. The demands that occur during the thesis work encourage students to be able to rise and adapt to face every difficulty they face. The ability of an individual to rise in the face of difficulties in his or her life is called resilience. One of the factors that affects the emergence of resilience in a person is self-acceptance. Self-acceptance plays a role in encouraging students to have a sense of optimism, so that students will try to remain calm in facing challenges and problems during the thesis work. The subject of this study is 254 students who are working on their thesis. The measuring tools used in this study are Berger's Self-Acceptance Scale and The Connor-Davidson Resilience Scale (CD-RISC). The results of this study found that there was a very weak significant positive relationship between self-acceptance and resilience, where the value of r = 0.246 and sig = 0.000 (p < 0.05). This means that the higher the level of self-acceptance, the higher the level of resilience. On the other hand, the lower the level of self-acceptance, the lower the level of resilience in students working on the thesis. The implications of this study are expected to make students who work on their thesis more able to develop self-acceptance, so that they can form resilience that helps students survive and rise to face the demands of working on their thesis. Selama pengerjaan skripsi mahasiswa akan dihadapkan dengan berbagai tuntutan. Tuntutan yang dihadapi oleh mahasiswa berupa aturan yang harus dipenuhi dalam mengerjakam skripsi, desakan dari orang tua, dan standar diri yang harus dicapai ketika mengerjakan skripsi. Tuntutan dan masalah yang terjadi selama mengerjakan skripsi mendorong mahasiswa agar mampu bangkit dan beradaptasi menghadapi setiap kesulitan yang dihadapi. Kemampuan individu untuk bangkit dalam menghadapi kesulitan di dalam hidupnya disebut dengan resiliensi. Salah satu faktor yang mempengaruhi timbulnya resiliensi pada diri seseorang adalah penerimaan diri. Penerimaan diri berperan untuk mendorong mahasiswa agar memiliki rasa optimis, sehingga mahasiswa akan berusaha agar tetap tenang dalam menghadapi tantangan maupun masalah selama pengerjaan skripsi. Subjek penelitian ini adalah 254 mahasiswa yang sedang mengerjakan skripsi. Alat ukur yang digunakan dalam penelitian ini adalah Berger’s Self-Acceptance Scale dan The Connor-Davidson Resilience Scale (CD-RISC). Adapun hasil dari penelitian ini ditemukan bahwa terdapat hubungan positif signifikan yang sangat lemah antara penerimaan diri dan resiliensi, dimana nilai r = 0,246 dan sig = 0,000 (p < 0,05). Artinya, semakin tingkat penerimaan diri maka semakin tinggi juga tingkat resiliensi. Sebaliknya, semakin rendah tingkat penerimaan diri maka semakin rendah tingkat resiliensi pada mahasiswa yang mengerjakan skripsi. Implikasi dari penelitian ini diharapkan mahasiswa yang mengerjakan skripsi agar lebih mampu mengembangkan penerimaan diri, sehingga dapat membentuk resiliensi yang membantu mahasiswa bertahan dan bangkit menghadapi tuntutan dalam mengerjakan skripsi.